Muara Bekasi – Muara Tawar Offshore Transmission Pipeline Routing and Economic Analysis. - Saputra, Asep Handaya; Ardiansyah, Ardiansyah (UI Scholars Hub, 2009)
Muara Bekasi – Muara Tawar Offshore Transmission Pipeline Routing and Economic Analysis. Power plant Muara Tawar will substitute the need of oil fuel to gas as form of economizing and energy conservation. The nearest supply point to fulfill natural gas needed on Muara Bekasi. So that Power Plant Company needed to develop gas pipeline infrastructure to joining the point.The purpose of this study is to create a system of gas transmission pipeline from gas supply point at Muara Bekasi to Power Plant Muara Tawar trough to offshore area. Design of gas transmission pipeline is started with technical data collection and supply-demand analyzing, continued with data analysis, rute construction and result of condition operation. The standard design of this design is DnV 2000. Gas demand in Power Plant Muara Tawar is 400 MMSCFD. From secondary data had been obtained total length of alternative route 3.7 km. Carbon Steel pipe diameter which had been used 22 inch nominal diameter. Gas supply pressure is 350 psig with pressure of demand point is setted on 500 psig. On pipeline system design the preesure before put in to compressor is around 321.7 psig. The design on bottom stability factor is the main concern. From the design calculation the total minimum pipe weight is 793.16 ton, whereas the design around 932.6 ton. Therefore, the pipe will be stable on bottom of sea.